Occurrence of Alkaloids in Grass Seeds Symbiotic With Vertically-Transmitted Epichloë Fungal Endophytes and Its Relationship With Antioxidants - Gundel, Pedro E.; Seal, Charlotte E.; Biganzoli, Fernando; Molina-Montenegro, Marco A.; Vázquez-de-Aldana, Beatriz R.; Zabalgogeazcoa, Iñigo; Bush, Lowell P.; Martínez-Ghersa, María A.; Ghersa, Claudio M. (Frontiers in Ecology and Evolution, 2018)
Host organisms can acquire new functional traits through symbiosis. Seed-transmitted Epichloë fungal endophytes are known to protect host plants against herbivores and increase tolerance to abiotic stresses by alkaloids and antioxidants, respectively (currencies of mutualism). Whereas alkaloids are fungal products with demonstrated effects at plant vegetative stage, few studies have focused on alkaloids in seeds. We assessed the occurrence of fungal alkaloids and determined their concentration in seeds of two host grasses, Festuca rubra and Lolium multiflorum. Then, we sought for a relationship with the antioxidants tocochromanols and glutathione, which are involved in the control of oxidative stress. Different alkaloids were detected depending on the species and plant genotype. Most notably, loline alkaloids were not detected in F. rubra seeds, whereas ergovaline and peramine were absent in L. multiflorum. In F. rubra, ergovaline concentration was dependent on the maternal line in interaction with the production year, diminishing in seeds after one year of storage. The exposure of L. multiflorum plants to ozone had no effect on the seed concentration of lolines. There was a positive relationship between concentrations of ergovaline and tocochromanol in both species, and between ergovaline concentration and EGSSG/2GSH (glutathione half-cell reduction potential) in RAB maternal line of F. rubra. These results suggest that alkaloid and antioxidants have a close association in seeds of host grasses, and that the alkaloid bioactivity could be related with the antioxidant capacity to control stress. This has important implications for the ecology of partner species, thus supporting its consideration for further research.